Systematic site selection solar-powered electric vehicle charging stations: A novel approach to sustainable transportation - Amir Naseri; Ali Roghani Araghi; Marziyeh Razeghi; Younes Noorollahi (Energy Strategy Reviews)
This research proposes a new approach to increase the utilization of electric vehicles (EVs) by establishing solar-powered charging stations. Using ArcGIS 10 8.2 software, the optimal locations for the construction of these stations were identified and all technical, economic, environmental, and geological aspects were studied more carefully. Diverging from prior research, the initiative of this research leverages public spaces such as gas stations and eco-lodges to reduce operational costs and enhance station sustainability. This method is globally applicable and sets a precedent for CO2 emission reduction within the transportation sector. Comparative and evaluative analyses of the solar electricity charging infrastructures that support the EVs with regard to the technical and functional parameters are performed. The systematic and innovative concept that has been put forward enables us to identify the places with the highest prospects regarding the construction of Solar-Powered Charging Stations for EVs across the world. As for the case of using this technique in the selected region, it proved that 18 % of the area of Qeshm Island is suitable for constructing solar-based EV-charged stations, and the demand the island will supply by 2040. In the studied region, it was determined that the type of vehicles has a significantly greater impact on energy consumption than the distance traveled by the vehicles. By opting for fuel-efficient vehicles, it is possible to supply approximately 74.96 % of the required energy through solar energy, and these vehicles can even be used for public services such as taxis that cover long distances. The findings indicate that by 2040, the area could transition 11 % of its vehicles to EVs, potentially decreasing CO2 emission by more than 34 tons.